A Study on Microlearning Through TikTok: Utilizing Social Media Videos for English Language Learning - Wijayanti, Sheila; Zulianingrum, Ana; Muhjaj, Juniya Bintang (Jurnal Ilmiah Profesi Pendidikan, 2025)
The microlearning approach will be combined with the use of social media platforms, namely TikTok videos, in English language learning. Microlearning is a learner-centered approach that offers short, focused learning units with interactive multimedia accessible across multiple devices. Research using the microlearning approach aims to make English learning in the classroom more flexible and effective in delivering learning materials because it can convey content in the smallest parts for easy understanding. The study will use a descriptive qualitative method with data collection techniques through observation, filling out pre-tests and post-tests, and documentation. The results of study indicate that the dominant micro skills are speaking (43%), writing (24%), listening (18%), and reading (15%). On the other hand, the second pie chart reveals that macro skills mainly focus on speaking (68%), with a smaller percentage in writing (13%), listening (13%), and reading only (6%). Thus, by combining innovative approaches such as microlearning and leveraging the popularity of social media platforms, educators can create interactive and engaging learning experiences for learners. The combination of microlearning, social media platforms, and English language teaching can offer valuable opportunities for learners to improve their language skills in a fun and interactive way. As technology advances in education, implementing these approaches can result in a more effective and dynamic language learning experience.